Peran Gaya Pengasuhan Reasoning dengan Perkembangan Sosio-Emosional Anak Usia Dini di Wilayah Pesisir Kota Mataram - Efan Yudha Winata; Rahma Talitha; Hema Alini Manihuruk; Avira Pebrina Syalsabilla; Najiah Ratna Willis (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the relationship between reasoning parenting styles and the socio-emotional development of early childhood children aged 4-6 years in the coastal area of ​​Mataram City. This parenting style is characterized by the provision of logical explanations, two-way communication, and recognition of the consequences of children's actions. This study uses a quantitative correlational approach with a total sampling technique, involving all members of the population who meet the research criteria with a sample of 44 pairs of parents and early childhood children from three PAUD schools in the coastal area of Mataram City. The research instruments consist of the Parenting Style and Diensions Questionnaire (PSDQ) and the Milestone Checklist. Data analysis was carried out using descriptive statistics and the Pearson Product Moment correlation test to determine the relationship between reasoning parenting and children's socio-emotional development. The statistical results of reasoning parenting in mothers showed a higher score (M = 4.13) than fathers (M = 3.90). Socio-emotional development in children is in the adequate to optimal category, with a percentage of 4-year-olds reaching 81%, 5-year-olds reaching 69%, and 6-year-olds reaching 100%. The Pearson correlation test yielded a significant coefficient of r=0.56 (p<0.01), with a contribution of 31.4%. These findings underscore the importance of communication-based parenting practices and logical explanations in supporting early childhood development in coastal areas.